Colorectal Cancer: A Total Provincial Experience with Survival Analysis - B.H. Weinerman; K.B. Orr (Canadian Journal of Gastroenterology)
A review of 1212 cases of colorectal cancer from the Manitoba Tumour Registry from 1974 through 1976 was done in order to establish survival rates for a total population, to examine the role of tumour differentiation and stage of disease on survival. and to examine the incidence of disease in the rural and urban populations. Stage was the most important factor in determining survival although the difference between stages C1 and C2 disease was not significant. However, a continuing relapse rate was seen in all patients with any type of infiltrating disease (B1 and B2 There appeared to be continuing relapse patterns in all those groups to at least 96 months. Histology was also an independent predictor of survival even when controlling for stage of disease. Some patients with well differentiated colorectal cancers with stage D disease (over 10%) were alive at 42 months. Age was not found to be a significant factor in survival except for those individuals over 71-years-old and sex was not an important factor. There was increased incidence of co lo rectal cancer in urban as opposed to rural populations, suggesting that possible differences in lifestyle may play a role in causation.